GSM mobile SMS/MMS using public key infrastructure: m-PKI - Anuar, N.B.; Kuen, L.N.; Zakaria, O.; Gani, Abdullah; Wahab, A.W.A. (2008)
Presently, mobile handheld device has successfully replaced traditional telephone to become the most popular wireless communication tools. Mobile Short Message Service (SMS) and Multimedia Message Service (MMS) fulfill almost all the user requirements as an effective communication and information delivering service. Since SMS/MMS become so popular on daily communication, there is a demand to communicate or exchange confidential information in a secure environment. Public Key Infrastructure (PKI) is a proven solution, which using pairing of key, for secure communication encryption. In this paper, m-PKI is introduced to provide PKI encryption to the mobile SMS and MMS. This new approach allows the end-user to send private and classified message via SMS. The key pair generation and distribution are performed by the Certificate Authority (CA). The size of the key pair are studied and decided by the tradeoff between performance and security.